SISTEM PENDUKUNG KEPUTUSAN PENDISTRIBUSIAN OBAT ( Studi Kasus : DINAS KESEHATAN KABUPATEN SOLOK) - JUFRIADIF NAAM (Jurnal Processor, 2010)
Effectiveness decision making very needed to assist human being in a company ororganisation to be yielding decision which with quality. Support reserved for variousdifferent managerial level, start from top head until division under him. By collectingdata with the method interview and other method, analyse by using logic and model tomanipulation of input data and data in database to yield wanted output. With existence ofthis decision support system, is expected by Pharmacy Warehouse can solve the problemof drugs distribution